Laurence Sterne : the Critical Heritage. - Howes, Alan B. (Routledge, 1995)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.